The spatial distribution of congener-specific human PCB concentrations in a PCB-polluted region - Strémy, Maximilián (Sci Total Environ, 2018)
Serum PCB congener concentrations were measured in 602 adults living near a PCB pollution source in eastern Slovakia. We created iso-concentration maps for 21 PCB congeners by geocoding each participant’s place of residence and kriging. Concentrations of PCB congeners were inversely associated with the distance of the participants’ residence from the source of pollution. Congener-specific risk factors were derived, particularly for PCBs 52 and 153. We observed that the spatial distribution of serum concentrations was influenced by micro-climatic parameters and physicochemical properties of the congeners. PCB congener profiles strongly correlated with that of the PCB commercial product Delor 106, which was manufactured in the region. The iso-concentration maps indicate that the zones with the highest predicted congener concentration have a mean area of approximately 235.75 ± 188.56 km(2) and the mean enrichment of concentration of congeners in serum in these zones is about 5.12 ± 1.36. We estimate that depending on congener approximately 23 457±18 762 individuals with PCB concentrations exceeding health-based guidance values live in these zones.